Использование методов интеллектуального анализа данных при разработке элементов систем ДО - Чалый, С. Ф. (УАДО, 2002)
The problem of distributed information training system elements development and data mining approach in this field is considered. Data mining evolutionary approach is proposed for this problem solution. Evolutionary algorithm based on genetic and evolutionary programming is considered
Keywords: дистанционное обучение; образование